Pengaruh Proses Pengeringan Tradisional terhadap Komposisi Proksimat Nike Ikan Payangkah (Ophieleotris aporos) dari Danau Tondano - Sofia Satriani Krisen; Ardi Kapahang (Jurnal Kimia Fullerene, 2019)
The research on effect of traditional drying process againt proximate composition of the payangkah fish nike has been done. A number of payangkah fish nike samples has been taken from the Tondano lake, divided into two parts, i,e, fresh samples and other parts were traditionally dried at temperature range of 37°C for 24 hours. The proximate composition of wet and dried samples respectively specified was water content of 83.157%, protein 13.128%, lipid 1.48%, ash 2.033%, crude fiber 0.65% and carbohydrate 0.2%. While for dry samples the water content of 9.59%, protein 67.434%, ash 5.065% and crude fiber 0.64%. The results shows that traditional drying process has positive influence against some parameters on proximate composition of the payangkah fish nike.